Heavy metal pollution increases CH4 and decreases CO2 emissions due to soil microbial changes in a mangrove wetland: Microcosm experiment and field examination. (April 2021) - Ma, Jiaojiao; Ullah, Sami; Niu, Anyi; Liao, Zhenni; Qin, Qunhao; Xu, Songjun; Lin, Chuxia
Abstract: Mangrove plays an important role in modulating global warming through substantial blue carbon storage relative to their greenhouse gas emission potential. The presence of heavy metals in mangrove wetlands can influence soil microbial communities with implications for decomposition of soil organic matter and emission of greenhouse gases. In this study, field monitoring and a microcosm experiment were conducted to examine the impacts of heavy metal pollution on soil microbial communities and greenhouse gas fluxes. The results show that heavy metal pollution decreased the richness and diversity of the overall soil microbial functional groups (heterotrophs and lithotrophs); however, it did not inhibit the activities of the methanogenic communities, possibly due to their stronger tolerance to heavy metal toxicity compared to the broader soil microbial communities. Consequently, the presence of heavy metals in the mangrove soils significantly increased the emission of CH4 while the emission of CO2 as a proxy of soil microbial respiration was decreased. The soil organic carbon content could also buffer the effect of heavy metal pollution and influence CO2 emissions due to reduced toxicity to microbes. The findings have implications for understanding the complication of greenhouse gas emissions by heavy metal pollution in mangrove wetlands. Graphical abstract: Image 1 Highlights: Field monitoring and microcosm experiment to investigate polluted mangrove soils. Examine impacts of heavy metals and other soil properties on greenhouse gas fluxes. Heavy metal pollution decreased richness and diversity of overall soil microbes. Methanogenic communities tolerated metal toxicity and their activities were thus not inhibited. Heavy metal pollution tended to decrease CO2 emission but enhance CH4 emission.